PI3K activity in dendritic cells exerts paradoxical effects during autoimmune inflammation. (July 2019) - Datler, Hannes; Vogel, Andrea; Kerndl, Martina; Baumgartinger, Christina; Musiejovsky, Laszlo; Makivic, Nina; Frech, Sophie; Niederreiter, Birgit; Haider, Thomas; Pühringer, Marlene; Brunner, Julia Stefanie; Sharif, Omar; et al.
Highlights: Dendritic cell (DC) expressed PI3K restrains cytokine secretion and antigen presentation. DC expressed PI3K dampens EAE associated TH 1 and TH 17 responses. PI3K activity in DCs but not macrophages or neutrophils worsens autoimmunity. Detrimental effects of DC expressed PI3K in EAE are dependent on IFN-γ. Abstract: The peripheral activation of autoreactive T cells and subsequent central nervous system (CNS) immune cell infiltration are key events relevant for experimental autoimmune encephalomyelitis (EAE), a commonly employed multiple sclerosis (MS) model, influenced by TH 1 and TH 17 mediated immunity. The phosphoinositide-3-kinase (PI3K)-AKT kinase pathway modulates outcome during EAE, with direct actions of PI3K on adaptive immunity implicated in deleterious and effects on antigen presenting cells involved in beneficial responses during EAE. Here, by genetically deleting the regulatory subunit of Class Ia PI3K, p85α, in selective myeloid cells, we aimed to resolve the impact of PI3K in EAE. While genetically deleting PI3K in LysM expressing cells exerted unremarkable effects, attenuating PI3K function in CD11c + dendritic cells (DCs), promoted secretion of pathogenic EAE promoting cytokines, particularly skewing TH 1 and TH 17 immunity, while notably, improving health in EAE. Neutralizing IFN-γ activity using blocking antibodies revealed a prolonged TH 1 response was critical for the decreased disease of these animals. Thus, PI3K-AKT signaling in DCs acts in a paradoxical manner. While attenuating EAE associated TH 1 and TH 17 responses, it impairs health during autoimmune inflammation.